Left ventricular wall motion during diastolic filling in endurance-trained athletes - Schmidt-Trucksäss, A.; Schmid, A.; Haussler, C.; Huber, G.; Huonker, M.; Keul, J. (Medicine & Science in Sports & Exercise, 2001)
Purpose: The purpose of this study was to assess left ventricular (LV) wall motion in highly endurance-trained athletes to evaluate LV diastolic function in physiologically hypertrophied hearts. Background: Diastolic filling dynamics have previously been examined in endurance-trained athletes by measuring pulsed-wave mitral inflow velocities during the early and atrial filling phase, indicating an unimpaired LV function. Assessment of LV wall motion may give additional information about the LV diastolic function in endurance-trained athletes. Methods: Left ventricular mass (LVM) and volume (LVV) were determined by M-mode echocardiography. Peak LV wall motion in the region of the basal septum close to the mitral anulus were measured during the early rapid and atrial filling phase by tissue Doppler in 30 endurance-trained athletes (T) and 16 sedentary control subjects (C) presumed to be healthy. Results: Myocardial LVM and LVV in T (LVM 159.4 +/- 18.0 g.m-2, LVV 100.4 +/- 13.0 mL.m-2) were significantly higher than in C (LVM 105.7 +/- 12.0.m-2, LVV 70.1 +/- 11.9 mL.m-2), and heart rate (HR) was significantly lower (HR C: 69.6 +/- 11.0 bpm, T 50.9 +/- 8.7 bpm),which is consistent with endurance training (P < 0.01 for both). Peak LV wall motion during the early rapid filling phase did not differ significantly between the groups (T: 10.69 +/- 1.46cm.s-1; C: 10.61 +/- 1.52 cm.s-1). Peak atrial wall motion was significantly lower in T (4.53 +/- 0.84 cm.s-1) versus C (5.74 +/- 0.75 cm.s-1), and the ratio of peak early diastolic to atrial wall motion was consequently higher in athletes (P < 0.01 for both). Conclusion: Regional wall motion at the basal septum near the mitral anulus during the early rapid filling phase is not altered by an increase in LVM or LVV when associated with endurance training.